Community Bonds and Canada’s Foundations: Rethinking Risk and Financial Outcomes - Quenneville, Rheann; Hebb, Tessa (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale, 2025)
Community wealth building (CWB) offers a place-based approach to impact investing, fostering local economic development and wealth retention (Dowin Kennedy, 2021; Guinan & O’Neill, 2019; O’Neill & Howard, 2018; Ratner, 2019). Community bonds (CBs), a CWB tool, challenge traditional wealth models but remain underutilized due to limited awareness (Surman & Hughes, 2012; Hughes, 2013). This study examines risk perceptions versus financial performance in the Canadian CB market, arguing that addressing information asymmetry is key to unlocking capital and scaling impact. Using historical repayment data, it introduces a dataset of CB offerings and proposes a bond rating system to reduce risk. The study also develops an investor typology and explores partnerships among investors, issuers, and intermediaries through a CWB lens.